The Titanic secret [compact disc, unabridged] : an Isaac Bell adventure - Cussler, Clive; Du Brul, Jack B (Cussler, Clive. Isaac Bell novels, 2019)
When NUMA Director Dirk Pitt finds a document inside an antiquated submersible left behind a century earlier by legendary detective Isaac Bell, it reopens a mystery involving an international power scheme aimed at seizing control of a rare element.